First measurements of periodicities and anisotropies of cosmic ray flux observed with a water-Cherenkov detector at the Marambio Antarctic base - Santos, Noelia Ayelen; Dasso, Sergio Ricardo; Gulisano, Adriana Maria; Areso, Omar Antonio; Pereira, Matias Hernan; Asorey, Hernán Gonzalo; Rubinstein, Lucas (Advances in Space Research)
A new water-Cherenkov radiation detector, located at the Argentine Marambio Antarctic Base (64.24S-56.62 W), has been monitoring the variability of galactic cosmic ray (GCR) flux since 2019. One of the main aims is to provide experimental data necessary to study interplanetary transport of GCRs during transient events at different space/time scales. In this paper we present the detector and analyze observations made during one full year. After the analysis and correction of the GCR flux variability due to the atmospheric conditions (pressure and temperature), a study of the periodicities is performed in order to analyze modulations due to heliospheric phenomena. We can observe two periods: (a) 1 day, associated with the Earth's rotation combined with the spatial anisotropy of the GCR flux; and (b) ∼ 30 days due to solar impact of stable solar structures combined with the rotation of the Sun. From a superposed epoch analysis, and considering the geomagnetic effects, the mean diurnal amplitude is ∼ 0.08% and the maximum flux is observed in ∼ 15 h local time (LT) direction in the interplanetary space. In such a way, we determine the capability of Neurus to observe anisotropies and other interplanetary modulations on the GCR flux arriving at the Earth. Fil: Santos, Noelia Ayelen. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias de la Atmósfera y los Océanos; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria; Argentina Fil: Dasso, Sergio Ricardo. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Física; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Astronomía y Física del Espacio. - Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Astronomía y Física del Espacio; Argentina. Universidad de Buenos Aires. Facultad de ...